Demencia senil en una paciente mayor de edad del centro de ayuda del GAD Municipal del cantón Echeandía - Coloma Ibarra, Jhostyn Bolney (2021)
The present work was prepared in order to evaluate dementia and old age in an older adult, which is why the changes that occur in old age with dementia were exposed. Since this is not an experimental work, the information was obtained from documents, scientific journals, health manuals among others, with reference to old age and dementia. With this information that was obtained and with the use of techniques that were used, reaching conclusions that will be useful for future research related to this topic. As it could be concluded, one of the aspects in which an individual is most at risk to develop a pathology is in old age related to cognition, since in this stage of life called old age the body suffers a significant physical and psychological deterioration, which can generate unwanted attitudes and situations in their environment.